Serotonin 1B receptor density mapping of the human brainstem using positron emission tomography and autoradiography. Issue 4 (April 2022) - Veldman, Emma R; Varrone, Andrea; Varnäs, Katarina; Svedberg, Marie M; Cselényi, Zsolt; Tiger, Mikael; Gulyás, Balázs; Halldin, Christer; Lundberg, Johan
The serotonin 1B (5-HT1B ) receptor has lately received considerable interest in relation to psychiatric and neurological diseases, partly due to findings based on quantification using Positron Emission Tomography (PET). Although the brainstem is an important structure in this regard, PET radioligand binding quantification in brainstem areas often shows poor reliability. This study aims to improve PET quantification of 5-HT1B receptor binding in the brainstem. Volumes of interest (VOIs) were selected based on a 3D [ 3 H]AZ10419369 Autoradiography brainstem model, which visualized 5-HT1B receptor distribution in high resolution. Two previously developed VOI delineation methods were tested and compared to a conventional manual method. For a method based on template data, a [ 11 C]AZ10419369 PET template was created by averaging parametric binding potential (BPND ) images of 52 healthy subjects. VOIs were generated based on a predefined volume and BPND thresholding and subsequently applied to test-retest [ 11 C]AZ10419369 parametric BPND images of 8 healthy subjects. For a method based on individual subject data, VOIs were generated directly on each individual parametric image. Both methods showed improved reliability compared to a conventional manual VOI. The VOIs created with [ 11 C]AZ10419369 template data can be automatically applied to future PET studies measuring 5-HT1B receptor binding in the brainstem.